Research handbook on transnational diaspora entrepreneurship - Sternberg, Rolf G.; Elo, Maria; Levie, Jonathan; Amorós, José Ernesto (Edward Elgar Publishing, 2023)
"This comprehensive Research Handbook provides insights into entrepreneurship across a range of country contexts, migration corridors and national policies to provide a collection of conceptual, empirical and policy-focused findings addressing transnational diaspora entrepreneurship. Chapters illustrate the phenomenon, considering what it is, how it works and how it is regulated. Contributions from top scholars in the field underline the view that transnational diaspora entrepreneurship is a socio-cultural as well as an economic phenomenon of increasing worldwide relevance in shifting economic, technological and political landscapes. Conceptual and methodological developments are presented from multiple perspectives, embedding unique country- and- context-based empirical research. Split into four key thematic sections, this Research Handbook first provides readers with an overview of the topic, before delving into country-specific case studies, migration corridors and their impacts, and then finally exploring the policy implications. Entrepreneurship scholars and students-particularly those with a focus on global entrepreneurship, diasporas, migration and international entrepreneurship-will find this a timely and important read. It will also be of value to administrators of entrepreneurial and migration programs, business developers, investment and startup agencies, diaspora organisations, NGOs and think-tanks"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung